The national school food program (pnae): source, changes and impacts - Silva, Eliane Regina Francisco da [UNESP]; Hespanhol, Rosangela Aparecida de Medeiros [UNESP] (Univ Federal Roraima, 2023)
The objective of this article is to show the origin, characteristics, implementation and changes of the PNAE through the analysis of the financial transfers and acquisitions of family agriculture for the said program at national and state scales of Sao Paulo in the period of 2012 to 2016 and impacts to family farmers and students. We seek to expose some of the characteristics and changes of the PNAE and to identify the strengths and limitations of the program. The methodological procedures used were the bibliographical survey and the consultation on the website of the National Fund for the Development of Education (FNDE). The results showed that the PNAE has contributed to the socioeconomic reproduction of the rural producers and has collaborated to improve the diet of the students and, consequently, in their school performance. However, the per capita value passed on by the federal government is low and the complementation of state and municipal resources is insufficient or non-existent. In addition, the obligation to purchase at least 30% of the resources destined by FNDE for products derived from family agriculture was not respected, at the federal and state scales, between 2012 and 2016.
Keywords: PNAE. Financial transfers. Family farming